Prevalence of breastfeeding in premature infants with very low birth weight in the first six months of life - doi: 10.4025/actascihealthsci.v35i2.11805 - Anelize Helena Sassá; Cauana Gonçalves Lopes; Talita Maria Bengozi; Edilaine Giovanini Rossetto; Sarah Nancy Deggau Hegeto de Souza; José Carlos Dalmas (Universidade Estadual de Maringá, 2013)
Few studies have investigated the duration of breastfeeding among premature infants born with very low birth weight. The prevalence of exclusive breastfeeding among very low birth weight premature infants at a university hospital in Londrina Paraná State, Brazil and the identification of factors related to breastfeeding practice were determined. Current quantitative and analytic retrospective study analyzed the medical records, attendance reports and interviews of 54 mother-infant binomials. Breastfeeding was prevalent in 90% of infants, of which 50% were exclusively breastfed, at hospital discharge. However, 51% were weaned before their sixth month. The statistical analysis showed a positive association between breastfeeding and do not working mothers outside the home, cesarean delivery, positive previous experience in breastfeeding and gestational age at birth over 33 weeks. MF prevalence in the specific population NBVLW infants reinforce the notion that breastfeeding preterm infants, albeit challenging, may be carried out with the appropriate support of the mother-child binomial.